PRELIMINARY PHYTOCHEMICAL ANALYSIS AND ANTIMICROBIAL ACTIVITY ETHANOLIC EXTRACTS OF DRIED FRUITS OF SOLANUM TORVUM (FAMILY-SOLANACEAE) - Kalita, Lawrence; Dash, Biswajit; Borah, Uttam; Deka, Juman; Dash, Suvakanta (International Journal of Current Pharmaceutical Research, 2017)
Objective: To study the antimicrobial activity ethanolic extracts of dried fruits of Solanumtorvum (family-solanaceae) along with preliminary phytochemical analysis. Methods: The ethanolic extract of dried fruits of the herb Solanumtorvum (family-solanaceae) were prepared and analyzed for phytochemical constituents using standard methods. The antimicrobial activity of the plant extracts were examined against 2 bacterial strains among one is gram positive and other is gram negative and 2 fungus using agar well diffusion method. Results: The present experiment shows the phytochemical analysis, antimicrobial activity of the ethanolic extract of dried fruits of the plant Solanumtorvum (family-solanaceae). Various phytochemical analysis revealed the presence of alkaloids, saponin, flavonoids, carbohydrates, glycosides, Steroids, proteins and amino acids and tannins. All the extracts of the plant showed antimicrobial activity against most of the test organisms. Conclusion: It can be concluded ethanolic extract of whole aerial parts of the Solanumtorvum (family-solanaceae) contain the high presence of phytochemicals. This extract was found to possess promising antimicrobial activity when compared with the standards.